Lipid nanoparticles from L. meyenii Walp mitigate sepsis through multimodal protein corona formation - Junsik J. Sung; Jacob R. Shaw; Josie D. Rezende; Shruti Dharmaraj; Andrea L. Cottingham; Mehari M. Weldemariam; Jace W. Jones; Maureen A. Kane; Ryan M. Pearson (Molecular Therapy: Methods & Clinical Development)
Plant-derived lipid nanoparticles (PDNPs) are nano-sized particles isolated from various edible plants that contain bioactive components involved in regulating biological responses. Here, we isolated maca-derived lipid nanoparticles (MDNPs) from Lepidium meyenii Walp (maca), evaluated their therapeutic effects using two representative lethal models of sepsis, and determined their multimodal anti-inflammatory mechanism that relied on broad sequestration and neutralization of multiple pro-inflammatory cytokines and acute phase proteins (APPs) through formation of a protein corona. Lipidomics of MDNPs revealed triacylglycerols and phytoceramides as major constituents. In vitro studies showed that MDNPs were non-toxic, reduced macrophage activation, and sequestered lipopolysaccharide (LPS)-induced pro-inflammatory cytokines, while mitigating nuclear factor kappa B (NF-κB) activity. In a pre-established LPS-induced endotoxemia model, MDNP treatment significantly reduced systemic pro-inflammatory cytokines, reduced organ damage, and increased survival. Untargeted proteomics and bioinformatics analysis identified an enrichment in APPs present in MDNP protein coronas and corresponding inflammatory pathways modulated. The efficacy of MDNPs were further tested using a lethal polymicrobial sepsis model, where treatment significantly improved survival even in the absence of antibiotics. This study identifies MDNPs as an effective strategy capable of inducing potent anti-inflammatory responses, offering significant therapeutic potential for diseases such as sepsis, while informing the future design of synthetic lipid nanoparticles.